(untitled) (Global Journal of Management and Business Research, 2015)
Female Entrepreneurship is considered an important tool for female empowerment and emancipation. The main objective of this study is to investigate female undergraduate students’ attitudes toward and perceptions of entrepreneurship (Comparison Ethiopian Public and Private Universities). Entrepreneurship has become a crucial area to study and understandespecially with respect to, attitudes toward entrepreneur, motivations, constraints and consequences. Female undergraduates students are chosen for the current study is because they are at a period in their career development where they are considering different career routes and are therefore, a potential source of future female entrepreneurs